ANALISIS YURIDIS KERUSAKAN DONBASS ARENA STADIUM DALAM KONFLIK BERSENJATA NON-INTERNASIONAL DI UKRAINA DALAM PERSPEKTIF HUKUM HUMANITER - Chairul, Dahril Darmawan; Jayakusuma, Zulfikar; Putri, Adi Tiara (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2018)
Humanitarian Law provides legal protection against civilian objects in international armed conflicts and non-international armed conflicts. However, in practice the legal protection is still being violated by one of the conflicting parties causing damage to civilian objects, as happened to Donbass Arena Stadium in non-international armed conflict in Ukraine.The purpose of this thesis is to find out the provision of International Humanitarian Law in non-international armed conflict especially the destruction of civilian objects and to find out the destruction of Donbass Arena Stadium in non-international armed conflict in Ukraine is the violation on International Humanitarian Law.The attack on civilian objects in non-international armed conflicts is seen as a violation of the rules of jus in bello, in which violation of the in bello juice is seen as a war crime. The destruction of Donbass Arena Stadium in non-international armed conflict in Ukraine is the violation on International Humanitarian Law and the provisions of the relevant Humanitarian Law for the destruction of Donbass Arena Stadium the essensially lies in the responsibility of the state, in other words, Ukraine as a State party to the Second Protocol II Amendment CCW 1996, is obliged to make national laws and administer legal proceedings against any violations that occurred when the armed conflict took place in his country.Keyword: Civilian Objects – Damage-Ukraine-Donbass Arena Stadium